The Relationship Between Cardiovascular Disease in Pregnancy and Fetomaternal Outcomes at Arifin Achmad Regional General Hospital (JURNAL IBU DAN ANAK, 2026)
Cardiovascular disease during pregnancy contributing to high rates of maternal and neonatal morbidity and mortality. In Indonesia, cardiovascular disease complications account for approximately 30% of maternal deaths, while about 34% of infants born to mothers with cardiovascular disease experience neonatal complications. This study aimed to determine the association between cardiovascular disease in pregnancy and fetomaternal outcomes. This quantitative study employed an analytical retrospective design using medical record data from January 2024 to December 2025. The sample consisted of 301 respondents selected via total sampling. Data were analyzed Chi-Square test with a 95% confidence level (α=0.05). The results revealed a significant association between cardiovascular disease in pregnancy and the incidence of LBW (p=0.000; OR=3.557), preterm birth (p=0.011; OR=1.899), asphyxia (p=0.010; OR=1.941), and fetal distress (p=0.001; OR=2.738); however, no significant association was found with IUFD (p=0.702). Therefore, it is recommended that Arifin Achmad Hospital enhance early detection, optimize antenatal monitoring, and implement multidisciplinary management to prevent maternal and neonatal complications.
Keywords: Cardiovascular disease in pregnancy; Low birth weight (LBW); Prematurity; Asphyxia; Fetal distress; Intrauterine fetal death (IUFD)